Desarrollo de un diagnóstico de las actividades de workover en los pozos representativos del campo Apiay para el establecimiento de indicadores adecuados de evaluación (2019)
This degree project proposes an optimal time indicator for well intervention activities in Apiay Field, through the evaluation of non-productive times in each activity carried out.